Does trade liberalization increase the formal-informal wage-gap in Pakistan? - Aslam, Noreen; Ul-Haq, Jabbar; Cheema, Ahmed Raza; Visas, Hubert (Edelweiss Applied Science and Technology, 2022)
This study assesses the influence of the 1988 trade liberalization on the formal-informal wage gap (FIFWG) using micro-level manufacturing sector data from 1990 to 2005 in Pakistan. As trade liberalization affects both the formal and informal sectors’ production capabilities, wage differentials between the two sectors’ workers are expected. We employed Wage Premium Methodology (WPM), Oaxaca-Blinder decomposition, restricted least squares, and weighted least squares (WLS) regression models for empirical analysis. Our study finds that trade liberalization has an impact on the formal-informal wage gap on the observable characteristics as well as on the unobservable characteristics. This formal-informal wage gap in Pakistan has widened as a result of trade liberalization. After controlling for many sector-related variables, our findings are robust. Lagged-trade policy and the formal-informal wage gap are also strongly associated. Our results remain insensitive when using the three different approaches (i.e., the wage premium methodology, the wage gap methodology, and the residual wage gap). To benefit from trade liberalization, sensible labor market flexibility is a prerequisite. This study contributes to existing literature in the case of Pakistan in the following ways: firstly, the reduction in protection rates as a proxy for trade liberalization is used. This proxy is a policy-based proxy that captures the pure effects of trade policy as compared to outcome-based proxies (i.e., trade ratios). Secondly, this investigation considers the whole trade-regime as a study period to inspect the core impacts of the trade regime, as import tariffs radically decreased during this regime. Thirdly, we calculate two variables of FIFWG (i.e., wage premiums, and residual wage gap) for analysis. Fourthly, we employ manufacturing industry panel data for empirical analysis.